Water extract from artichoke ameliorates high-fat diet-induced non-alcoholic fatty liver disease in rats - Aihua Deng; Fengying Liu; Xuchong Tang; Yun Wang; Peng Xie; Qifu Yang; Bing Xiao (figshare, 2022)
Abstract Background The “multiple-hit” hypothesis is currently the most widely accepted theory for non-alcoholic fatty liver disease (NAFLD) pathogenesis. The present study aimed to investigate the effects of the water extract of artichoke (WEA) on NAFLD and its underlying mechanism. Methods Rats were fed a high-fat diet (HFD) for 8 weeks to induce NAFLD and then treated with WEA at three doses (0.4, 0.8, and 1.6 g/kg body weight, BW) for 8 weeks. At the end of the intervention, serum biochemical parameters, hepatic antioxidant capacity, hepatic levels of pro-inflammatory cytokines, liver histopathology, hepatic inflammatory gene and lipid metabolism gene expression, and Akt and p-Akt (S473) protein levels were determined. Results The body weight, liver weight, liver triglyceride (TG) and serum levels of TG, total cholesterol, low-density lipoprotein cholesterol, alanine aminotransferase, aspartate aminotransferase, glucose, and insulin were all significantly reduced in the WEA-treated groups (0.8 and 1.6 g/kg BW) compared with the HFD group (P < 0.01). A significant decrease in hepatic content of malondialdehyde (P < 0.01) and glutathione (P < 0.01), as well as a significant increase in liver superoxide dismutase activity (P < 0.01) were observed in WEA-treated groups (0.8 and 1.6 g/kg BW) compared to the HFD group. In addition, there was a marked decrease in the hepatic levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) in the WEA-treated groups compared to the HFD group (P < 0.01). In line with these findings, the histopathology of the livers of rats treated with WEA (0.8 and 1.6 g/kg BW) showed a decrease in steatosis, ballooning, and lobular inflammation. Mechanistically, the reduced hepatic TG content might be related to the downregulation of lipogenic genes (SREBP1c, FASN, SCD1) and upregulation of lipolytic gene (PPARα), and the improved insulin signaling might be associated with the observed increase in antioxidant activity and reduction in inflammation in the WEA-treated groups. Conclusion The hepatoprotective role of WEA in NAFLD may be attributed to its anti-steatotic, antioxidant, anti-inflammatory, and anti-insulin resistance effects.
Keywords: Biochemistry; Medicine; Genetics; Molecular Biology; Physiology; Pharmacology; Chemical Sciences not elsewhere classified; Immunology